2022
DOI: 10.1109/access.2022.3151898
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Industry 4.0 Technologies on Manufacturing Strategies: Proposition of Technology-Integrated Selection

Abstract: Industry 4.0 (I4.0) has increasingly been adopted as an advanced manufacturing strategy to counter global competition. The capability of a company to compete on various manufacturing strategy outputs (MSOs) such as cost, quality, delivery, flexibility, performance and innovativeness play a significant role in motivating the whole company to take advantage of its competitors. I4.0 is comprised of various technologies, and how I4.0 technologies can influence the MSOs are still unclear, and it took less interest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 104 publications
(131 reference statements)
0
9
0
Order By: Relevance
“…Here, we propose a detailed taxonomy of manufacturing strategy in the era of industry 4.0 to implement cutting-edge technologies based on the experts' opinions. MS 4.0 can be defined as - MS 4.0 can build an organized structure with the highest world-class level of capability and align infrastructure accordingly to adopt the suitable I4.0 technologies to utilize their benefits to the fullest extent, which in turn enhances the MS outputs in terms of competitive priorities (Abdullah et al, 2022). The steps to formulate MS 4.0 are discussed next.…”
Section: Manufacturing Strategy 40taxonomy and Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…Here, we propose a detailed taxonomy of manufacturing strategy in the era of industry 4.0 to implement cutting-edge technologies based on the experts' opinions. MS 4.0 can be defined as - MS 4.0 can build an organized structure with the highest world-class level of capability and align infrastructure accordingly to adopt the suitable I4.0 technologies to utilize their benefits to the fullest extent, which in turn enhances the MS outputs in terms of competitive priorities (Abdullah et al, 2022). The steps to formulate MS 4.0 are discussed next.…”
Section: Manufacturing Strategy 40taxonomy and Frameworkmentioning
confidence: 99%
“…The incipient I4.0 technologies pose a noteworthy threat to the organizations willing to implement I4.0 while investing because of the probable financial losses associated with them, resulting in no investment recovery (Lee and Lee, 2020). Apart from this, Abdullah et al (2022) identified that each I4.0 technology can be suitable for achieving a particular competitive priority. Porter and Heppelmann (2014) stated that the output of the industry 4.0 enabled smart factories will be the smart connected products, which can help reshape the industries to offer new competitive opportunities and achieve competitive advantage.…”
Section: 25mentioning
confidence: 99%
See 3 more Smart Citations